The Role of Shadow Teacher in Improving Autistic Students Ability in Learning - Al Sabatin, Ibrahim Mahmoud (Advances in Social Sciences Research Journal, 2020)
Shadow teaching is a professional service offered to the school and family to better manage the needs of students who have a learning difference. Shadow teachers are employed by the parents to work with their child at school. This study tries to answer the following questions: what is the role of the shadow teacher in the classroom? To what extent do shadow teacher help in improving students' ability in learning? What are the key elements for successful shadow teaching? To achieve the purpose of the study, the researcher prepared a questionnaire concerning the questions of the study and observed the shadow teacher's performance in the class room in the American Academy Nablus. Means, standard deviations and percentages were calculated by using SPSS program. The present study revealed the following results: Shadow teacher plays an important role in providing additional support, throughout the school day, academically and psychologically, to those students enrolled in the Optimal Learning (OL) program that need this additional support. In the light of the present study, the researcher recommended providing Palestinian schools with shadow teachers to help students with special need.